BETWEEN VERSES, PROSES AND POETRY: THE IMPORTANCE OF ART IN JUVENILE SOCIABILITY - Bonalume, Bruna Carolina [UNESP]; Manelli, Jessica Pereira [UNESP] (Fundacao Univ Tocantins, 2021)
This article is a theoretical reflection based on the report of the authors' professional experience in the socio-cultural project SambaVida, located in the interior of Sao Paulo and aims to discuss the contributions of artistic experiences in the process of personal, social and citizen formation of adolescents and young people. The discussions put in, therefore, emerge from the everyday,from the empirical experience, this being the place of speech from which these narratives and theoretical reflections intentionally start. It is this daily life that reveals to us that art and its multiple expressions allows these subjects to reflect and build knowledge about the world around them. This perspective resides in the recognition that a cultural experience is expressed in different ways and allows adolescents and young people to reflect and awaken critical awareness, which expands the possibilities of resignifying the spaces they live in and their placement in these contexts, as protagonists of history itself.
Keywords: Adolescence; Youth; Artistic Manifestations